Preclinical evaluation of the potential PARP-imaging probe [carbonyl-11C]DPQ - Katarína Benčurová; Theresa Balber; Victoria Weissenböck; Lukas Kogler; Joachim Friske; Verena Pichler; Markus Mitterhauser; Marcus Hacker; Cécile Philippe; Marius Ozenil (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Poly (ADP-ribose) polymerase (PARP) enzymes are crucial for the repair of DNA single-strand breaks and have become key therapeutic targets in homologous recombination-deficient cancers, including prostate cancer. To enable non-invasive monitoring of PARP-1 expression, several PARP-1-targeting positron emission tomography (PET) tracers have been developed. Here, we aimed to preclinically investigate [carbonyl-11C]DPQ as an alternative PARP-1 PET tracer as it features a strongly distinct chemotype compared to the frontrunners [18F]FluorThanatrace and [18F]PARPi. Results [carbonyl-11C]DPQ was synthesised in a GE TracerLab FXC2 module, yielding sufficient activity (940 ± 410 MBq), molar activity (53 ± 16 GBq/µmol) and radiochemical purity (> 97%) for subsequent preclinical evaluation. [carbonyl-11C]DPQ showed high stability in formulation, in human plasma, and when incubated with human liver microsomes. In vitro, similar specific uptake was observed in both PC3 prostate cancer cells and CHO-K1 Chinese hamster ovary cells. However, in vivo studies using fertilised chicken eggs (in ovo model) revealed poor and non-displaceable tumour accumulation in PC3-derived xenografts, despite confirmed vascularisation and PARP-1 expression. Rapid uptake was observed in the liver (10 min), with less than 30% of the intact compound remaining in the liver 70 min post-injection. Conclusions Although [carbonyl-11C]DPQ demonstrated metabolic stability and specific binding in vitro, suboptimal tumour-targeting properties and pronounced liver metabolism were observed in ovo. Therefore, further animal experiments with mammalian models were not indicated.